2015
DOI: 10.1650/condor-14-165.1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and movements of Alaska-breeding Steller's Eiders in the nonbreeding period

Abstract: Abstract. Annual spring aerial surveys were initiated in 1992, and repeated in 1993, 1994, 1997, 1998, 2000, 2001, 2002, 2003, 2004 and 2005 to monitor the population status of and habitat use by Steller's eiders (Polysticta stelleri) migrating northward in southwestern Alaska. Since the timing of migration varies, two to three replicate shoreline surveys were conducted each spring through 1997, to increase the probability of encountering the entire population of eiders as they transited the survey area en r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Steller's Eider use of distinct breeding, molting and wintering habitat may allow us to generate more informed hypotheses regarding the Labrador Duck range and biology. Steller's Eider breeding occurs around freshwater ponds in the arctic coastal plains of the Alaskan North Slope and in Siberia; they then migrate to shallow protected embayments to molt in the autumn (Petersen et al 2006;Martin et al 2015), and ice free shallow water habitats in winter. A major Steller's Eider molting ground on Novoya Zemla (Petersen et.…”
Section: Phylogenetics and Inferred Ecology Of C Lawi And C Labradomentioning
confidence: 99%
“…Steller's Eider use of distinct breeding, molting and wintering habitat may allow us to generate more informed hypotheses regarding the Labrador Duck range and biology. Steller's Eider breeding occurs around freshwater ponds in the arctic coastal plains of the Alaskan North Slope and in Siberia; they then migrate to shallow protected embayments to molt in the autumn (Petersen et al 2006;Martin et al 2015), and ice free shallow water habitats in winter. A major Steller's Eider molting ground on Novoya Zemla (Petersen et.…”
Section: Phylogenetics and Inferred Ecology Of C Lawi And C Labradomentioning
confidence: 99%
“…King eiders are far more abundant than common eiders in this region (Quakenbush et al 2009), which is reflected in numbers taken by hunters. Spectacled eiders and Steller's eiders also migrate along this corridor (Sexson et al 2014; Martin et al 2015), but are federally threatened and therefore not legally hunted. Repeated benthic sampling from 1999 to 2010 in the northern Bering Sea indicated that the dispersion of large areas of high prey density may shift over periods as short as 5–6 years (Lovvorn et al 2009, 2014), apparently with strong effects of changes in currents driven by prevailing winds.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we used published values for marine invertebrate prey from nearshore habitats of the Bering and Chukchi Seas (Dunton et al, 1989(Dunton et al, , 2012Lovvorn et al, 2015). These values represent prey available to sea ducks during their spring migration between wintering sites and the breeding ground (Figure 1), with some fraction of these duck populations known to stage in this region before moving inland to breeding sites (Lovvorn et al, 2015;Martin et al, 2015;Oppel & Powell, 2009b;Sexson et al, 2014). We selected marine prey taxa to include in our analyses based on those included in Lovvorn et al (2015) for King Eiders collected along the Chukchi Sea coast, and on dietary and foraging studies of all four species in other regions (Blicher et al, 2011;Bustnes & Erikstad, 1988;Bustnes & Galaktionov, 2004;Bustnes & Systad, 2001;Jamieson et al, 2001;Lovvorn et al, 2003;Merkel et al, 2007;Ouellet et al, 2013;Petersen et al, 1998;White & Veit, 2020;Žydelis & Ruškytė, 2005).…”
Section: Sample Collection and Processingmentioning
confidence: 99%